Lung Herniation as a Complication of Chronic Obstructive Pulmonary Disease - Rushan Momin; Tylin Siwemuke; Alexander Warner; Yao Kang (Annals of Internal Medicine: Clinical Cases)
Lung herniation is a rare complication of chronic obstructive pulmonary disease. This case describes a patient with a history of chronic obstructive pulmonary disease and laryngeal and thyroid carcinoma treated with total laryngectomy who presented with dysphagia, nasal regurgitation, and shortness of breath. Computed tomography imaging confirmed severe emphysema with herniation of the right lung apex through the thoracic inlet. Although this complication is uncommon, providers should recognize its presenting symptoms, especially in patients with risk factors.